Consumers’ Attitude towards the Cruelty-Free Label on Cosmetic and Skincare Products and Its Influence on Purchase Intention - Elisa Christianti Wuisan; Agustinus Februadi (Journal of Marketing Innovation (JMI), 2022)
Many brands, especially in Indonesia, are starting to apply cruelty-free labels on their products currently. However, the absence of legal certainty, lack of consumers’ awareness, and the number of companies who still use animal testing methods make this research important. Therefore, this study aims to determine consumers’ attitudes toward cruelty-free labels on cosmetics products and their effects on purchase intention. In determining the sample, this study uses a non-probability sampling method. In addition, this study uses environmental knowledge and moral obligation variables as determinants of attitude and purchase intention in cruelty-free cosmetics products as the dependent variables. Questionnaires were distributed to 211 participants, starting from the age of 17 years old in Indonesia, specifically in DKI Jakarta and West Java areas. The results show a positive and significant influence on the determinant variable of attitude which in turn affects purchase intention. Based on the analysis that has been done, the respondents have a positive attitude toward cruelty-free cosmetics products.